2000
DOI: 10.1097/00004872-200018020-00010
|View full text |Cite
|
Sign up to set email alerts
|

Baseline reproducibility of B-mode ultrasonic measurement of carotid artery intima – media thickness

Abstract: The results demonstrate that by implementing standardized protocols and strict quality control procedures, highly reliable ultrasonic measurements of carotid artery IMT can be achieved in large multi-national trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(73 citation statements)
references
References 11 publications
4
67
0
2
Order By: Relevance
“…The effect of semi-automated edge detection on the extent of reduction in measurement variability depends on the contribution of sonographers and readers to the total variability. A number of studies have indicated that differences between sonographers have a relatively larger effect on the CIMT measurements than differences between readers [15][16][17]. Indeed, reproducibility results from a study with images that were read using semi-automated edge detection were similar to those reported from other studies in which CIMT reading was performed manually [16].…”
Section: Introductionsupporting
confidence: 62%
“…The effect of semi-automated edge detection on the extent of reduction in measurement variability depends on the contribution of sonographers and readers to the total variability. A number of studies have indicated that differences between sonographers have a relatively larger effect on the CIMT measurements than differences between readers [15][16][17]. Indeed, reproducibility results from a study with images that were read using semi-automated edge detection were similar to those reported from other studies in which CIMT reading was performed manually [16].…”
Section: Introductionsupporting
confidence: 62%
“…ca-IMT measurements are widely used in observational studies to evaluate determinants and consequences of atherosclerosis (26)(27)(28)(29). Several studies have shown that increased ca-IMT confers risk of future coronary heart disease and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…According to the ELSA trial, the mean of the maximum IMT of the four far walls of the carotid bifurcations and the common carotid arteries (CBM max ) showed the highest reproducibility of ultrasound measurements (coefficient of reliability: 0.872), and the overall single maximum IMT ('Max-IMT' in the present study) also showed high reproducibility (coefficient of reliability: 0.794). 16 Although PS and Mean-IMT also showed significant association with target organ damage, the procedures of measuring them are relatively complicated and the reliability of the measurements is spatially dependent. Max-IMT measurement is quite simple and straightforward, because it is performed by only measuring the maximum thickness of intima-media including plaques.…”
Section: Discussionmentioning
confidence: 99%